2020
DOI: 10.1016/j.heliyon.2020.e03854
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of the alkaline deproteinization of Nile-tilapia skin for the production of collagen

Abstract: A new phenomenological model, based on a second order dissolution kinetics, was developed for the alkaline removal of non-collagenous protein (NCP) from the skin of Nile tilapia (SNT). This model allows estimating the liquid concentration of NCP in terms of temperature, skin size, NaOH concentration and time. This model was fitted with 135 experiments averaging a R 2 of 0.99. The root-mean-square deviation and the mean-absolutepercentage error of the model were 0.0041 and 3.15%, respectively. The Arrhenius-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…12 Another finding indicated that removing non-collagenous protein from Nile tilapia skin was most efficient at 20 °C. 50 This study was also the first to report that skin size has the most impact on NaOH pre-treatment, with smaller skin sizes able to eliminate more noncollagenous protein due to larger surface area. Extensive studies evaluating collagen extraction from Bester sturgeon by-products with and without NaOH pre-treatment demonstrated that the alkaline method expedited the extraction process but significantly reduced yield.…”
Section: Conventional Processes For Collagen Production Chemical Pre-...mentioning
confidence: 77%
See 3 more Smart Citations
“…12 Another finding indicated that removing non-collagenous protein from Nile tilapia skin was most efficient at 20 °C. 50 This study was also the first to report that skin size has the most impact on NaOH pre-treatment, with smaller skin sizes able to eliminate more noncollagenous protein due to larger surface area. Extensive studies evaluating collagen extraction from Bester sturgeon by-products with and without NaOH pre-treatment demonstrated that the alkaline method expedited the extraction process but significantly reduced yield.…”
Section: Conventional Processes For Collagen Production Chemical Pre-...mentioning
confidence: 77%
“…12 Acetic acid concentration up to 1 mol L −1 has a direct effect on collagen recovery from the skin of small-spotted catshark (Scyliorhinus canicula). 50 However, the maximum collagen recovery from sole fish skin occurred at 0.6 mol L −1 and decreased gradually thereafter. It was suggested that the charge density of collagen is determined by the concentration of acetic acid in the extraction medium, which also influences its electrostatic interaction and structure, as well as its solubility and extractability from raw materials.…”
Section: Acid Extractionmentioning
confidence: 92%
See 2 more Smart Citations
“…In order to evaluate the structural characteristics, a Fourier transform infrared spectroscopy analysis was performed using a Thermo Scientific Nicolet iS50. The attenuated total reflectance technique (ATR) was used in a 4000–600 cm −1 range with a 4 cm −1 resolution [ 39 ].…”
Section: Methodsmentioning
confidence: 99%